Directions of health education of families taking care of patients who suffered stroke in secondary prevention measures - Hebel, Kazimiera; Lesińska-Sawicka, Małgorzata; Waśkow, Monika (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Stroke is the main cause of disability of the people at the age of over 40 in Poland. Family care for the member of the family who is a chronic or disabled patient is an essential form of a help offered to these kind of patients. Currently ill and his family are increasingly perceived as partners in health-care professionals. Educational actions are a kind of partnership. The scope of information and educational support depends on shortages in education. Objective is to provide the most important directions of health education, addressed to the members of the families of patients who suffered stroke. Main aims of poststroke education is an improvement of a patient’s functional condition, reduction of physical and mental load, preventing disease complications resulting from reduced fitness and a stroke secondary prevention. Expected benefits include an appropriate lifestyle promotion, improvement of physical and mental condition of a patient and his or her members of the family and a knowledge increase dealing with the essence of strokes. Nursing Topice 2010; 18 (4): 497-502